A method for preparing Ga-containing nanocrystals with adjustable bandgap and ultraviolet luminescence
By adjusting the stoichiometric ratio of zinc, indium and gallium precursors and adopting heteroepitaxial growth shell structure, combined with ZnF treatment, the problem of precise band gap regulation of zinc-based quantum dot materials within the ultraviolet emission range is solved, and efficient ultraviolet emission and excellent optical performance of nanocrystals are achieved.
Patent Information
- Application Number
- CN202411309535.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-09-19
AI Technical Summary
It is difficult to achieve precise band gap regulation in zinc-based quantum dot materials within the ultraviolet emission range, and the uneven element distribution and surface defect problems are more prominent.
By adjusting the stoichiometric ratio of zinc, indium, and gallium precursors, magic size clusters (MSCs) are used as precursors, and the ZnGaS transition shell and ZnS shell are grown through heteroepitaxial growth, combined with ZnF treatment, the band gap of nanocrystals and the reduction of surface defects are achieved.
Accurate control of the band gap of ZnInGaS nanocrystals is achieved, covering an ultra-wide band gap range of 3.2eV to 3.7eV, improving the ultraviolet emission efficiency and photoluminescence quantum yield of nanocrystals, and significantly reducing surface defects, and the emission wavelength can be adjusted between 366nm and 420nm.
Smart Images

Figure CN119193149B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor materials, and in particular to a method for preparing ultraviolet luminescent Ga-containing nanocrystals with adjustable band gap. Background Art
[0002] With the development of nanotechnology, colloidal semiconductor quantum dots have shown broad application prospects in the field of optoelectronic devices due to their excellent optical properties, good chemical stability and size-adjustable bandgap characteristics. Especially in the fields of ultraviolet photodetectors, light-emitting diodes (LEDs), displays, and optical sensors, nanocrystalline materials that can precisely control their luminescence wavelengths are increasingly valued. In traditional quantum dot materials, cadmium-based compounds (such as CdSe and CdTe) are often used to achieve adjustable band gaps and efficient luminescence performance. However, cadmium is toxic and is strictly restricted in environmentally friendly materials and applications. Therefore, in recent years, the development of non-cadmium-based quantum dot materials has become a research hotspot. Zinc-based sulfides (such as ZnS) have become ideal candidates for ultraviolet luminescence applications because of their inherent wide band gap (~3.7 eV) and low toxicity.
[0003] However, in practical applications, zinc-based quantum dot materials still have the following problems: it is challenging to achieve wide-range band gap regulation by simple stoichiometric ratio adjustment, especially in the ultraviolet emission range, where precise band gap regulation is difficult to achieve. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing ultraviolet luminescent Ga-containing nanocrystals with adjustable band gap, which solves the problem that it is difficult to achieve precise control of the band gap of zinc-based quantum dot materials.
[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing Ga-containing nanocrystals with adjustable bandgap ultraviolet luminescence, comprising the following steps:
[0006] S1: Precursor preparation
[0007] Add zinc precursor, indium precursor, gallium precursor, sulfur precursor, organic amine and 1-octadecene into a three-necked flask and mix well;
[0008] S2: Reaction condition setting
[0009] Initial reaction: The mixture was heated and maintained under nitrogen protection to form ZIGS MSCs;
[0010] Temperature-raising reaction: gradually raising the reaction temperature and maintaining it to promote the transformation of MSCs into ZnInGaS nanocrystals;
[0011] Cooling treatment: After the reaction is completed, the reaction solution is naturally cooled to room temperature;
[0012] S3: Precipitation and purification of nanocrystals
[0013] At room temperature, an antisolvent is added to the reaction solution to induce the precipitation of ZIGS nanocrystals;
[0014] The nanocrystals were collected by centrifugation and washed with n-hexane, and the washing was repeated three times to purify the resulting ZIGS nanocrystal suspension;
[0015] S4: Epitaxial growth of transition shell
[0016] Transition shell preparation: ZIGS core-shell nanocrystals were loaded with zinc acetate, gallium acetylacetonate, organic amine, organic acid and 1-octadecene in a three-necked flask and degassed to remove water and solvent;
[0017] Transition shell growth: The reaction solution is heated and a sulfur precursor solution is injected through a syringe pump to epitaxially grow a ZnGaS transition shell layer;
[0018] Post-treatment: After the reaction is completed, the mixture is cooled to room temperature, and an anti-solvent is added again to precipitate the nanocrystals. The ZIGS / ZnGaS nanocrystals with a transition shell are purified by centrifugation;
[0019] S5: Further growth of ZnS shell
[0020] Preparation of ZnS shell layer: The purified ZIGS / ZnGaS core-shell nanocrystals, zinc acetate, organic amine, and 1-octadecene were placed in a three-necked flask and degassed again;
[0021] Growth of ZnS shell layer: heating the reaction solution, and adding zinc oleate solution and sulfur precursor solution to perform epitaxial growth of ZnS shell layer;
[0022] Purification treatment: After cooling to room temperature, the nanocrystals are precipitated with acetone or ethanol solvent and washed repeatedly to obtain purified ZIGS / ZnGaS / ZnS nanocrystals.
[0023] Preferably, in the S1 step, the zinc precursor is preferably one or more of diethyl zinc, zinc acetate, zinc oleate or zinc halide, the indium precursor is preferably indium acetate, indium chloride or indium acetylacetonate, the gallium precursor is preferably gallium acetylacetonate or gallium chloride, the sulfur precursor is preferably sulfur powder, the organic amine is preferably a chain primary amine, including octadecylamine and / or oleylamine, and the organic acid is preferably octadecenoic acid.
[0024] Preferably, in the step S2, the initial reaction is: heating the mixture to 100-120° C. under nitrogen protection for 30 minutes,
[0025] Temperature reaction: Keep the reaction at 160°C, 200°C and 220°C in sequence, each time for 60 minutes, and finally keep it at 220°C for another 120 minutes.
[0026] Preferably, in step S3, the anti-solvent is a strong polar solvent miscible with n-hexane, including one or more of acetone, methanol and ethanol.
[0027] Preferably, in the step S4, the reaction solution is heated to 260° C., and the sulfur precursor solution is injected at a rate of 2.0 mL per hour through a syringe pump.
[0028] Preferably, in step S5, the reaction solution is heated to 280° C., and the zinc oleate solution and the sulfur precursor solution are added at a rate of 2.0 mL per hour.
[0029] Preferably, when synthesizing ZIGS MSCs, the molar ratio of the total amount of anion elements in the anion precursor solution to the zinc element in the zinc precursor is 1:1.
[0030] Preferably, the volume ratio of the organic amine to the organic acid is 4:1.
[0031] Preferably, in the step S1, uniformly mixing the zinc precursor, the indium precursor, the gallium precursor, the sulfur precursor, the organic amine and the 1-octadecene comprises: mixing the zinc precursor, the indium precursor, the gallium precursor, the sulfur precursor, the organic amine and the 1-octadecene, evacuating the air under the protection of nitrogen, heating to 100-120° C., and evacuating the air for 30 minutes; evacuating the ZIGS NCs, zinc acetate, gallium acetylacetonate, the organic amine, the organic acid and the 1-octadecene under the protection of nitrogen, heating to 100-120° C., and evacuating the air for 30 minutes.
[0032] The present invention provides a method for preparing ultraviolet luminescent Ga-containing nanocrystals with adjustable band gap, which has the following beneficial effects:
[0033] 1. The present invention can achieve precise control of the band gap of ZnInGaS (ZIGS) nanocrystals by adjusting the stoichiometric ratio of zinc, indium and gallium in the precursor, covering an ultra-wide band gap range of 3.2eV to 3.7eV. This makes the nanocrystals suitable for optoelectronic devices in different wavelength ranges, especially ultraviolet optoelectronic applications.
[0034] 2. The present invention uses magic size clusters (MSCs) as precursors to improve the problem of uneven element distribution in multi-element nanocrystals, ensure the uniform introduction of zinc, indium and gallium elements, and improve the overall stability and performance of nanocrystals.
[0035] 3. The present invention reduces the lattice mismatch between the core and shell by epitaxially growing the ZnGaS transition shell layer, enhances the quantum confinement effect, and thus significantly improves the ultraviolet emission efficiency and photoluminescence quantum yield (PLQY) of the nanocrystals.
[0036] 4. The invention introduces ZnF treatment to reduce the oxidation sites of Ga, effectively reduce the surface defects of nanocrystals, and further improve the optical performance, especially the luminous efficiency in the ultraviolet band. The treated nanocrystals show a higher PLQY of 18.3%.
[0037] 5. The nanocrystals of the present invention exhibit narrow-band emission in the ultraviolet band, and the emission wavelength can be adjusted between 366nm and 420nm. They have high optical properties and are suitable for high-demand ultraviolet photodetectors, optical sensors, display technologies and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 (a) UV-visible absorption spectra of ZIGS core NCs with different stoichiometric ratios of the present invention; (b) PL emission spectra. Black line (Zn:In:Ga=6:1:1), red line (Zn:In:Ga=3:1:2), blue line (Zn:In:Ga=1:1:1), light blue line (Zn:In:Ga=6:1:1, continued epitaxial growth). TEM images of ZIGS core NCs with different stoichiometric ratios, (c) Zn:In:Ga=6:1:1, (d) Zn:In:Ga=3:1:2, (e) Zn:In:Ga=6:1:1, (f) (after epitaxial growth), Zn:In:Ga=1:1:1.
[0039] Figure 2 (a) UV-visible absorption spectrum of the present invention; (b) PL emission spectrum. Blue line (ZIGS core NCs), light purple line (ZIGS / ZGS core / shell (C / S) NCs), purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs), dark purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs treated with ZnF). The stoichiometric ratio of all the above ZIGS core NCs is Zn: In: Ga = 1: 1: 1. TEM images: (c) ZIGS core NCs, (d) ZIGS / ZGS core / shell (C / S) NCs, (e) ZIGS / ZGS / ZnS core / shell / shell (C / S / S).
[0040] Figure 3The XRD pattern of the present invention, the standard diffraction peaks of cubic ZnS (JCPDS No.: 097-018-1741), tetragonal zinc gallium selenide (ZGS) (JCPDS No.: 097-063-5300) are given at the top and bottom, respectively. Blue line (ZIGS core NCs), light purple line (ZIGS / ZGS core / shell (C / S) NCs), purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs), dark purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs treated with ZnF). DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Please see attached Figure 1 - Attachment Figure 3 The present invention provides a method for preparing a Ga-containing nanocrystal with adjustable bandgap and ultraviolet light emission, comprising the following steps:
[0043] S1: Precursor preparation
[0044] Zinc precursor: one or more of diethyl zinc (ZnEt2), zinc acetate (Zn(C2H3O2)2), zinc oleate (ZnOA) or zinc halide (such as ZnCl2) are selected.
[0045] Indium precursor: Select indium acetate (In(C2H3O2)3), indium chloride (InCl3) or indium acetylacetonate (In(acac)3).
[0046] Gallium precursor: choose gallium acetylacetonate (Ga(acac)3) or gallium chloride (GaCl3).
[0047] Sulfur precursor: Use high purity sulfur powder (S).
[0048] Organic amines: Select chain primary amines, such as octadecylamine (ODA) and / or oleylamine (OLA).
[0049] Organic acid: Octadecylacid (OA) was used.
[0050] Solvent: 1-Octadecene (ODE).
[0051] S2: Reaction condition setting
[0052] A zinc precursor (0.20 mmol, for example zinc acetate), an indium precursor (0.20 mmol, for example indium acetate), a gallium precursor (0.20 mmol, for example gallium acetylacetonate), OLA (5.0 mL), OA (1.0 mL) and ODE (5.0 mL) were added into a three-necked flask in proportion and mixed well.
[0053] The three-necked flask was connected to a Schlenk line and degassed with nitrogen three times to remove oxygen and moisture.
[0054] The flask was heated to 120°C and subjected to vacuum degassing at 120°C for 60 min to further remove moisture and impurities in the system.
[0055] The sulfur precursor (0.8 mL, 0.5 M sulfur solution in 2.00 mL OLA) was injected into the flask and maintained at 120 °C for 30 min to generate ZIGS MSCs;
[0056] S3: Precipitation and purification of nanocrystals
[0057] Reaction temperature control:
[0058] The reaction solution was gradually heated to 160°C and maintained at this temperature for 60 minutes.
[0059] The temperature was further raised to 200°C and maintained for 60 minutes.
[0060] Finally, the temperature was raised to 220 °C and maintained for 120 min to promote the transformation of MSCs into ZIGS nanocrystals.
[0061] Cooling and precipitation:
[0062] After the reaction was completed, it was cooled naturally to room temperature.
[0063] An anti-solvent (such as anhydrous ethanol) is added to the reaction solution to promote the precipitation of ZIGS nanocrystals.
[0064] The nanocrystals were collected by centrifugation and washed with n-hexane, and the washing was repeated three times to obtain a purified ZIGS nanocrystal suspension;
[0065] S4: Epitaxial growth of transition shell
[0066] Precursor preparation:
[0067] ZIGS / ZnGaS core-shell nanocrystals, zinc acetate (0.10 mmol, 0.018 g), gallium acetylacetonate (0.10 mmol, 0.037 g), OLA (5.0 mL), OA (1.0 mL) and ODE (5.0 mL) were charged into a three-necked flask.
[0068] Degassing treatment:
[0069] A Schlenk line was connected and degassing with nitrogen was performed three times.
[0070] The mixture was heated to 120°C and vacuum degassed at 120°C for 60 minutes to remove moisture and impurities.
[0071] Transition Shell Growth:
[0072] The reaction solution was heated to 260°C.
[0073] ODE-S (0.1 M) solution was injected into the reaction bottle at a rate of 2.0 mL / h through a syringe pump to promote the epitaxial growth of the ZnGaS transition shell layer.
[0074] After the reaction was completed, it was cooled to room temperature.
[0075] An anti-solvent (such as anhydrous ethanol) is added to the reaction solution to precipitate ZIGS / ZnGaS nanocrystals.
[0076] The ZIGS / ZnGaS core-shell nanocrystals with a ZnGaS transition shell layer were obtained by purification by centrifugation.
[0077] S5: Further growth of ZnS shell
[0078] Precursor preparation:
[0079] Purified ZIGS / ZnGaS core-shell nanocrystals (0.1 mmol), OLA (5.0 mL), OA (1.0 mL) and ODE (5.0 mL) were placed in a three-necked flask.
[0080] Degassing treatment:
[0081] A Schlenk line was connected and degassing with nitrogen was performed three times.
[0082] The mixture was heated to 120°C and vacuum degassed at 120°C for 60 minutes to remove moisture and impurities.
[0083] ZnS shell growth:
[0084] The reaction solution was heated to 280°C.
[0085] Zinc oleate (0.1 M), ODE-S (0.1 M) and n-dodecyl mercaptan (DDT) solution (1.0 mL) were added at a rate of 2.0 mL / h via a syringe pump to promote the epitaxial growth of the ZnS shell.
[0086] After the reaction was completed, it was cooled to room temperature.
[0087] An anti-solvent (such as anhydrous ethanol) is added to the reaction solution to precipitate ZIGS / ZnGaS / ZnS nanocrystals.
[0088] High-quality ZIGS / ZnGaS / ZnS core-shell nanocrystals were obtained by purification by centrifugation.
[0089] Then, ZnF treatment is performed to improve the optical performance
[0090] ZnF treatment steps:
[0091] The purified ZIGS / ZnGaS / ZnS core-shell nanocrystals are mixed with a ZnF solution (such as a 0.1 M ZnF solution in ODE, with a concentration of 100 mg / mL) in a certain ratio.
[0092] The reaction solution is treated at 220° C. for a certain period of time (eg, 20 minutes) to introduce ZnF and reduce oxidation sites of Ga.
[0093] Post-processing:
[0094] After cooling to room temperature, an anti-solvent (such as anhydrous ethanol) is added to precipitate ZIGS / ZnGaS / ZnS core-shell nanocrystals treated with ZnF.
[0095] The final product was purified by centrifugation, and the PL quantum yield (PLQY) was increased to 18.3%.
[0096] Bandgap control and property optimization
[0097] Control of stoichiometric ratio:
[0098] By adjusting the feed ratio of zinc, indium and gallium precursors (such as Zn:In:Ga=1:1:1, 6:1:1, 3:1:2, etc.), the band gap of ZIGS nanocrystals can be finely controlled, and the band gap range can cover 3.2eV to 3.7eV.
[0099] Lattice matching and quantum confinement effect enhancement:
[0100] By heteroepitaxially growing the ZnGaS transition shell layer, the lattice mismatch between the core and the shell is reduced, the quantum confinement effect is enhanced, and the ultraviolet emission performance is improved.
[0101] Effective suppression of surface defects:
[0102] Through the dual protection of ZnF treatment and epitaxial shell layer, the defects on the surface of nanocrystals are significantly reduced, and the PLQY and luminescence stability are improved.
[0103] Characterization and performance testing of nanocrystals
[0104] Ultraviolet-visible absorption spectrum (UV-Vis):
[0105] Measure the absorption edge of nanocrystals to evaluate the effect of bandgap manipulation.
[0106] Photoluminescence spectroscopy (PL)
[0107] The emission spectra after different stoichiometric ratios and different shell treatments were measured to evaluate the emission wavelength and quantum yield.
[0108] Transmission Electron Microscopy (TEM):
[0109] The morphology and size distribution of the nanocrystals were observed to verify the integrity of the core-shell structure.
[0110] X-ray Diffraction (XRD):
[0111] The crystal structure of the nanocrystals was analyzed to confirm the phase composition and crystalline quality of ZIGS, ZnGaS and ZnS.
[0112] refer to Figure 1 . (a) UV-Vis absorption spectra of ZIGS core NCs with different stoichiometric ratios; (b) PL emission spectra. Black line (Zn:In:Ga=6:1:1), red line (Zn:In:Ga=3:1:2), blue line (Zn:In:Ga=1:1:1), and light blue line (Zn:In:Ga=6:1:1, continued epitaxial growth). TEM images of ZIGS core NCs with different stoichiometric ratios, (c) Zn:In:Ga=6:1:1, (d) Zn:In:Ga=3:1:2, (e) Zn:In:Ga=6:1:1, (f) (after epitaxial growth), Zn:In:Ga=1:1:1.
[0113] Figure 2 (a) UV-visible absorption spectrum; (b) PL emission spectrum. Blue line (ZIGS core NCs), light purple line (ZIGS / ZGS core / shell (C / S) NCs), purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs), dark purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs treated with ZnF). The stoichiometric ratio of all the above ZIGS core NCs is Zn: In: Ga = 1: 1: 1. TEM images: (c) ZIGS core NCs, (d) ZIGS / ZGS core / shell (C / S) NCs, (e) ZIGS / ZGS / ZnS core / shell / shell (C / S / S).
[0114] Figure 3XRD patterns, standard diffraction peaks of cubic ZnS (JCPDS No.: 097-018-1741) and tetragonal zinc gallium selenide (ZGS) (JCPDS No.: 097-063-5300) are given at the top and bottom, respectively. Blue line (ZIGS core NCs), light purple line (ZIGS / ZGS core / shell (C / S) NCs), purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs), dark purple line (ZIGS / ZGS / ZnS core / shell / shell (C / S / S) NCs treated with ZnF). The stoichiometric ratio of all the above ZIGS core NCs is Zn:In:Ga=1:1:1.
[0115] The following is an introduction in conjunction with specific embodiments:
[0116] Example 1: Synthesis of ZIGS Nanocrystals
[0117] Raw materials preparation:
[0118] Zn(C2H3O2)2·2H2O: 0.20mmol (0.039g)
[0119] In(C2H3O2)3·3H2O: 0.20mmol (0.059g)
[0120] Ga(acac)3: 0.20mmol(0.074g)
[0121] OLA: 5.0mL
[0122] OA:1.0mL
[0123] ODE: 5.0mL
[0124] Formation of MSCs:
[0125] The above raw materials were added into a three-necked flask according to proportion and the flask was sealed and connected to a Schlenk line.
[0126] Nitrogen degassing was performed three times to ensure an oxygen-free environment.
[0127] The mixture was heated to 120°C and vacuum degassed at 120°C for 60 minutes to remove moisture.
[0128] 0.8 mL of sulfur precursor (0.5 M sulfur solution in 2.00 mL of OLA) was injected and the reaction was maintained at 120°C for 30 minutes to generate ZIGS MSCs.
[0129] Synthesis and precipitation of nanocrystals:
[0130] The reaction solution was gradually heated to 160°C and maintained at this temperature for 60 minutes.
[0131] The temperature was further raised to 200°C and maintained for 60 minutes.
[0132] Finally, the temperature was raised to 220°C and maintained for 120 minutes to complete the formation of ZIGS nanocrystals.
[0133] The mixture was cooled naturally to room temperature, and anhydrous ethanol was added as an anti-solvent to precipitate nanocrystals.
[0134] The purified ZIGS nanocrystal suspension was collected by centrifugation and washed three times with n-hexane.
[0135] Example 2: Preparation of ZIGS / ZnGaS core-shell nanocrystals
[0136] Precursor preparation:
[0137] Zn(C2H3O2)2·2H2O: 0.10mmol (0.018g)
[0138] Ga(acac)3: 0.10mmol(0.037g)
[0139] OLA: 5.0mL
[0140] OA:1.0mL
[0141] ODE: 5.0mL
[0142] Transition shell growth:
[0143] The above raw materials were mixed with 0.1 mmol ZIGS core-shell nanocrystals (n-hexane solution) and placed in a three-necked flask.
[0144] A Schlenk line was connected and degassing with nitrogen was performed three times.
[0145] The mixture was heated to 120°C and vacuum degassed at 120°C for 60 minutes.
[0146] The reaction solution was heated to 260° C., and 2.5 mL of ODE-S (0.1 M) solution was added at a rate of 2.0 mL / h through a syringe pump to promote the epitaxial growth of the ZnGaS transition shell layer.
[0147] After the reaction was completed, the mixture was cooled to room temperature and anhydrous ethanol was added to precipitate nanocrystals.
[0148] The ZIGS / ZnGaS core-shell nanocrystals with a ZnGaS transition shell layer were obtained by purification by centrifugation.
[0149] Example 3: Preparation of ZIGS / ZnGaS / ZnS core-shell nanocrystals
[0150] Precursor preparation:
[0151] Purified ZIGS / ZnGaS core-shell nanocrystals: 0.1mmol
[0152] OLA: 5.0mL
[0153] OA:1.0mL
[0154] ODE: 5.0mL
[0155] Growth of ZnS shell:
[0156] The above raw materials were placed in a three-necked flask, connected to a Schlenk line, and degassed with nitrogen three times.
[0157] The mixture was heated to 120°C and vacuum degassed at 120°C for 60 minutes.
[0158] The reaction solution was heated to 280° C., and 4 mL of zinc oleate (0.1 M) solution and 1 mL of DDT solution were added at a rate of 2.0 mL / h through a syringe pump to promote the epitaxial growth of the ZnS shell layer.
[0159] After the reaction was completed, the mixture was cooled to room temperature and anhydrous ethanol was added to precipitate ZIGS / ZnGaS / ZnS nanocrystals.
[0160] High-quality ZIGS / ZnGaS / ZnS core-shell nanocrystals were obtained by purification by centrifugation.
[0161] Example 4: ZnF treatment to improve PL performance
[0162] ZnF treatment steps:
[0163] Take the purified ZIGS / ZnGaS / ZnS core-shell nanocrystals and add an appropriate amount of ZnF solution (such as a 0.1 M ZnF solution in ODE, with a concentration of 100 mg / mL).
[0164] The mixed solution was heated to 220°C and maintained for 20 minutes to introduce ZnF into the nanocrystal structure and reduce the oxidation sites of Ga.
[0165] Post-processing:
[0166] After cooling to room temperature, anhydrous ethanol was added to precipitate the ZnF-treated nanocrystals.
[0167] The final ZIGS / ZnGaS / ZnS nanocrystals were purified by centrifugation, with the PL quantum yield (PLQY) increased to 18.3%, the emission wavelength range of 366nm to 420nm, and ultra-wideband ultraviolet narrowband emission characteristics with high optical performance.
[0168] Summary of optimization points
[0169] Precise control of element ratios:
[0170] By using MSCs as precursors, the effective introduction of Ga element was ensured, solving the problem of uneven element distribution in multi-element nanocrystals.
[0171] Efficient growth of epitaxial shell:
[0172] The ZnGaS transition shell layer is grown heteroepitaxially to reduce the lattice mismatch between the core and shell, enhance the quantum confinement effect, and improve the ultraviolet emission performance of the nanocrystals.
[0173] Suppression of surface defects:
[0174] Through ZnF treatment and multi-layer shell structure, the defects on the surface of nanocrystals are effectively reduced, and the photoluminescence quantum yield (PLQY) and luminescence stability are improved.
[0175] Bandgap tunability:
[0176] By adjusting the stoichiometric ratio of zinc, indium and gallium precursors, the band gap of ZIGS nanocrystals was finely controlled, covering an ultra-wide band gap range (3.2eV to 3.7eV).
[0177] Realization of high quality core-shell structure:
[0178] The epitaxial growth of multiple shell layers (ZnGaS and ZnS) ensures the high crystalline quality and excellent optical properties of the nanocrystals.
[0179] Effect and verification of the embodiment
[0180] The ZIGS / ZnGaS / ZnS core-shell nanocrystals prepared in the above embodiment were characterized by ultraviolet-visible absorption spectroscopy (UV-Vis), photoluminescence spectroscopy (PL), transmission electron microscopy (TEM) and X-ray diffraction (XRD), and the following effects were verified:
[0181] High PL quantum yield: The PLQY of the nanocrystals after ZnF treatment reaches 18.3%, showing excellent photoluminescence performance.
[0182] Narrowband emission: The emission wavelength can be widely tuned in the range of 366nm to 420nm, achieving ultra-wideband UV narrowband emission.
[0183] Excellent crystal quality: TEM images show a uniform core-shell structure, and XRD patterns confirm the high crystallinity of the ZIGS, ZnGaS, and ZnS phases.
[0184] Effective defect suppression: ZnF treatment significantly reduces the oxidation sites of Ga and improves the luminescence stability and efficiency of nanocrystals.
[0185] Application prospects
[0186] The high-quality ZIGS / ZnGaS / ZnS core-shell nanocrystals with adjustable band gap prepared by the present invention have broad application prospects due to their high PLQY, narrow-band emission and excellent ultraviolet emission performance, including but not limited to:
[0187] UV Photodetectors: Highly efficient UV light detection capabilities for environmental monitoring, medical diagnostics, and security applications.
[0188] Optical Sensors: For high-sensitivity UV light sensing applications.
[0189] Display technology: As a luminescent material in ultraviolet display devices, it provides high brightness and high color purity display effects.
[0190] Optical communication: As an efficient light source in ultraviolet light communication systems, it improves transmission efficiency and signal quality.
[0191] in conclusion
[0192] By optimizing the selection of precursors, precisely controlling the stoichiometric ratio, using heteroepitaxial growth of the transition shell layer, and introducing ZnF treatment, the present invention successfully prepared ZIGS / ZnGaS / ZnS core-shell nanocrystals with adjustable band gap and excellent optical properties, solving the problems of uneven element distribution and surface defects in the prior art, having broad application potential, and providing important material support for the development of future optoelectronic devices.
[0193] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing ultraviolet-luminescent Ga-containing nanocrystals with adjustable bandgap, characterized in that: The following steps are involved: S1: Precursor preparation Add zinc precursor, indium precursor, gallium precursor, sulfur precursor, organic amine and 1-octadecene into a three-necked flask and mix well; S2: Reaction condition setting Initial reaction: The mixture was heated and maintained under nitrogen protection to form ZIGS MSCs; Temperature-raising reaction: gradually raising the reaction temperature and maintaining it to promote the transformation of MSCs into ZnInGaS nanocrystals; Cooling treatment: After the reaction is completed, the reaction solution is naturally cooled to room temperature; S3: Precipitation and purification of nanocrystals At room temperature, an antisolvent is added to the reaction solution to induce the precipitation of ZIGS nanocrystals; The nanocrystals were collected by centrifugation and washed with n-hexane, and the washing was repeated three times to purify the resulting ZIGS nanocrystal suspension; S4: Epitaxial growth of transition shell Transition shell preparation: ZIGS core-shell nanocrystals were loaded with zinc acetate, gallium acetylacetonate, organic amine, organic acid and 1-octadecene in a three-necked flask and degassed to remove water and solvent; Transition shell growth: The reaction solution is heated and a sulfur precursor solution is injected through a syringe pump to epitaxially grow a ZnGaS transition shell layer; Post-treatment: After the reaction is completed, the mixture is cooled to room temperature, and an anti-solvent is added again to precipitate the nanocrystals. The ZIGS / ZnGaS nanocrystals with a transition shell are purified by centrifugation; S5: Further growth of ZnS shell Preparation of ZnS shell layer: The purified ZIGS / ZnGaS core-shell nanocrystals, zinc acetate, organic amine, and 1-octadecene were placed in a three-necked flask and degassed again; Growth of ZnS shell layer: heating the reaction solution, and adding zinc oleate solution and sulfur precursor solution to perform epitaxial growth of ZnS shell layer; Purification treatment: After cooling to room temperature, the nanocrystals are precipitated with acetone or ethanol solvent and washed repeatedly to obtain purified ZIGS / ZnGaS / ZnS nanocrystals.
2. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: In the step S1, the zinc precursor uses one or more of diethyl zinc, zinc acetate, zinc oleate or zinc halide, the indium precursor uses indium acetate, indium chloride or indium acetylacetonate, the gallium precursor uses gallium acetylacetonate or gallium chloride, the sulfur precursor uses sulfur powder, the organic amine chain primary amine includes octadecylamine or oleylamine, and the organic acid uses octadecyl amine.
3. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: In the step S2, the initial reaction is: the mixture is heated to 100-120° C. under nitrogen protection for 30 minutes. Temperature reaction: Keep the reaction at 160°C, 200°C and 220°C in sequence, each time for 60 minutes, and finally keep it at 220°C for another 120 minutes.
4. The method for preparing a Ga-containing nanocrystal with adjustable bandgap ultraviolet luminescence according to claim 1, characterized in that: In the step S3, the anti-solvent is a strong polar solvent that is miscible with n-hexane, including one or more of acetone, methanol and ethanol.
5. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: In the step S4, the reaction solution is heated to 260° C., and the sulfur precursor solution is injected at a rate of 2.0 mL per hour through a syringe pump.
6. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: In the step S5, the reaction solution is heated to 280° C., and the zinc oleate solution and the sulfur precursor solution are added at a rate of 2.0 mL per hour.
7. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: When synthesizing ZIGS MSCs, the molar ratio of the total amount of anion elements in the anion precursor solution to the zinc element in the zinc precursor is 1:
1.
8. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: The volume ratio of the organic amine to the organic acid is 4:
1.
9. The method for preparing a bandgap-adjustable ultraviolet-luminescent Ga-containing nanocrystal according to claim 1, characterized in that: In the step S1, uniformly mixing the zinc precursor, the indium precursor, the gallium precursor, the sulfur precursor, the organic amine and the 1-octadecene includes: mixing the zinc precursor, the indium precursor, the gallium precursor, the sulfur precursor, the organic amine and the 1-octadecene, evacuating the mixture under nitrogen protection, heating the mixture to 100 to 120° C., and evacuating the mixture for 30 minutes; evacuating the mixture of ZIGS NCs, zinc acetate, gallium acetylacetonate, the organic amine, the organic acid and the 1-octadecene under nitrogen protection, heating the mixture to 100 to 120° C., and evacuating the mixture for 30 minutes.
Citation Information
Patent Citations
Preparation method of narrow-band blue-light Cu-Ga-S / ZnS nanocrystal
CN116891738A
Preparation method of narrow-band green-light and red-light Ag-In-Ga-Zn-S nanocrystals
CN117866623A